MONITORING SIDE EFFECTS OF ANTITUBERCULOSIS DRUGS (OATS) IN PATIENTS WITH TUBERCULOSIS AT TUGUREJO REGIONAL GENERAL HOSPITAL SEMARANG - Yuliasari, Niken; Gloria, Fransisca; Dahliyanti, Novita Dwi; Ovikariani, Ovikariani; Sa’adah, Anifatus; Suwarni, Sri (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2025)
Monitoring of side effects of antituberculosis drugs (OAT) in tuberculosis (TB) patients during the intensive treatment phase. Tuberculosis, caused by Mycobacterium tuberculosis, requires the use of OAT which can cause a variety of side effects. Research shows that common side effects experienced by TB patients include joint pain, nausea, lack of appetite, and dizziness. The high incidence of these side effects has the potential to affect patient compliance in undergoing treatment, which has an impact on the success of TB therapy. The research method used is descriptive observation with a cross-sectional approach. Data was taken from patients undergoing treatment at various hospitals and health centers. The results showed that most patients experienced mild side effects, with frequency varying depending on the week of treatment. In the first week, almost all patients reported side effects, while the frequency tended to decrease over time. Regular monitoring of OAT side effects is essential to improve patient compliance and prevent treatment discontinuation. Health workers are expected to conduct periodic evaluations and provide support to patients to stay motivated. With effective monitoring, the risk of serious side effects can be minimized, and treatment outcomes for TB patients can be improved.